2011
DOI: 10.1590/s1984-29612011000400018
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of anti-Toxoplasma gondii antibodies in cattle and pigs slaughtered, State of Rio de Janeiro

Abstract: This study aimed to estimate the occurrence of anti-Toxoplasma gondii antibodies by means of the Indirect Immunufluorescent Antibody Assay (IFAT) in cattle and pigs from slaughterhouses in two municipalities in the State of Rio de Janeiro. IgG anti-T. gondii antibodies was found in 1.96% (9/459) of the cattle and 7.64% (31/406) of the pigs, without any positive association (p > 0.05) with risk factors for transmission and seropositivity. Taking the cutoff point of IFAT ³ 1:64, titers of 64 and 256 were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…In cattle, the seroprevalence estimated in the study is relatively low (3.92%), it is comparable to rates found in Brazil (1.96%), Iran (1.6%) and Poland (3.15%) as reported by Luciano et al (2011), Raeghi et al (2011 and Holec-Gąsior et al (2013), respectively. This seroprevalence and the rate of infected herds (12.82%) may reflect a low distribution of the parasite in the farms of the study area.…”
Section: Discussionsupporting
confidence: 79%
“…In cattle, the seroprevalence estimated in the study is relatively low (3.92%), it is comparable to rates found in Brazil (1.96%), Iran (1.6%) and Poland (3.15%) as reported by Luciano et al (2011), Raeghi et al (2011 and Holec-Gąsior et al (2013), respectively. This seroprevalence and the rate of infected herds (12.82%) may reflect a low distribution of the parasite in the farms of the study area.…”
Section: Discussionsupporting
confidence: 79%
“…Studies on frequency of antibodies for T. gondii among pigs in Brazil have indicated that the seropositivity rates are between 7.64% and 43.1% in farms with different production systems (MOURA et al, 2007;MILLAR, et al, 2008;MURARO et al, 2010;LUCIANO et al, 2011;CORRÊA et al, 1978;CAVALCANTE et al, 2006;SAMICO FERNANDES et al, 2012;SOUSA et al, 2014;AZEVEDO et al, 2010). Accordingly, IFA was the serological technique used in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Brazil have reported serological evidence of exposure to T. gondii among pigs in the states of São Paulo (CORRÊA et al, 1978), Rondônia (CAVALCANTE et al, 2006), Paraná (MOURA et al, 2007), Paraíba (AZEVEDO et al, 2010), Bahia (BEZERRA et al, 2009, Mato Grosso (MURARO et al, 2010), Pernambuco (FERNANDES et al, 2012), Piauí (SOUSA et al, 2014 and Rio de Janeiro (LUCIANO et al, 2011). However, no studies in the state of Rio Grande do Norte have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of beef in the transmission of toxoplasmosis is unknown (GARCIA et al, 2012). Surveys conducted in slaughterhouses in Brazil showed that seropositivitity in beef cattle ranged from 1.96 to 41.4% (DAGUER et al, 2004;LUCIANO et al, 2011). Thus, beef, which is the most consumed meat in the country, may be an important source of infection for humans, especially in areas where the frequency of human infection is high, such as the state of Pará in the Brazilian Amazon region (CARMO, 2011).…”
Section: Introductionmentioning
confidence: 99%